Emergence capacity and seedlings early growth of four legumes in arid zones under NaCl-stress - Ruiz-Espinoza, Francisco; Reyes-Perez, Juan; Beltrán-Morales, Felix; Murillo-Amador, Bernardo; Rodríguez-Ortiz, Juan; Arce-Amézquita, Pablo (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
Legumes are used as fodder and green manures, because of fix nitrogen biologically. The objective of this study was to determine the emergence capacity and the early growth of four legume species treated with different NaCl-stress concentrations. The experiment was established in a completely randomized design with a factorial arrangement, where the first factor was the four legumes’ species (Vigna unguiculata L. Walp., Lablab purpureus (L.) Sweet, Clitoria ternatea L. and Canavalia ensiformis L. DC.) and the second factor was NaCl concentrations (0.25, 50, and 75 mM) with 16 treatments and four replications. The variables evaluated were emergence rate and percentage, stem and root length, fresh and dry weight of stem+leaves and root, stem and root length, stem diameter and the ratio of stems+leaves dry weight and roots dry weight (plant balance). The results showed that all variables expressed significant differences between species, NaCl and the species × NaCl interaction. A differential response between legumes to NaCl stress was observed. The most tolerant species to NaCl were Vigna unguiculata and Canavalia ensiformis showed a higher tolerance with respect to Lablab purpureus and Clitoria ternatea.